Measures of Economic Inequality Focusing on the Status of the Lower and Middle Income Groups. Issue 1 (1st January 2016) - Gastwirth, Joseph L.
ABSTRACT: The substantial increase in economic inequality in favor of the upper income group in the United States and many other developed and developing nations during the past 30 years has become a major concern in public policy. Modifications of the standard measures of inequality, the Lorenz curve and Gini index, are proposed that better reflect the decline in the share of income received by the poor and middle portions of the income distribution relative to the upper end. A second pair of curves based on the fractions of either the middle or lower portion of the income curve that has the same share as the top u % and the areas between them and the line of equality are introduced. The proposed curves and related measures indicate that a noticeably greater change in the U.S. income distribution occurred during the 1967–2013 time period than are observed in the Lorenz curve and Gini index. The maximum difference between the proposed curves for the income and wealth data in the United Kingdom's 2010–2012 survey are greater than that of the Lorenz curve.